THE PROVERBIAL AND PSYCHOLOGICAL MEANINGS OF “WHO’S YOUR DADDY?” - Bronner, Simon J. (Proverbium - Yearbook, 2014)
At the end of the twentieth-century and early twenty-first century, “Who’s Your Daddy?” spontaneously chanted by large crowds at sporting events in the United States drew national press attention. Journalists usually reported the ritualized chanting of the question being of recent origin, but differed over whether it was meant to be offensive or endearing. In this essay, I use linguistic, paremiological, historical, folkloristic, and ethnographic research to show that the phrase could be considered a “proverbial interrogative” indicating social dominance associated with patriarchy and probably dates to the American frontier experience in the mid-nineteenth century. Through the twentieth century, it became associated with African-American street culture and the “beat scene,” often with sexual connotations. In its latest iteration, I argue with reference to “frame theory” that the frame of sports allowed for psycho-logical projection in this and other folk sayings of anxieties about declining power of men in a feminizing American society.